An Analysis and Generation Toolbox for Chaotic Substitution Boxes: A Case Study Based on Chaotic Labyrinth Rene Thomas System - Ozkaynak, Fatih (Springer Int Publ Ag, 2020)
One of the successful examples of chaos-based cryptology design proposals is s-box structures based on random selection. There are many s-box design proposals in the literature since chaotic systems are a powerful entropy source. This feature is one of the most important factors affecting successful designs. Another important factor affecting this success is that measurable test criteria for s-box analysis are clearly presented in the literature. This study has developed a toolbox that can analyze these measurable test criteria. This toolbox has shown that the performance measures of the seven previous proposals in the literature are incorrectly calculated. This analysis toolbox has been made free to use for researchers and aims to prevent inaccurate analyses in future studies. Another contribution of the study is the random selection-based s-box generator toolbox. This toolbox can use both classical random function and chaotic system classes as entropy source. Another important output of generator toolbox is the chaotic labyrinth Rene Thomas system, which can be selected as a continuous-time chaotic system. This system has been first used in the s-box generator. This study has been one of the first steps in addressing the analysis problems of the chaos-based cryptology literature. It is thought that along with such studies to be developed in the future will positively affect the success of the chaos-based cryptographic system proposals.
Keywords: Substitution box; S-box; S-box analysis toolbox; S-box generation toolbox; Chaos; Chaotic labyrinth Rene Thomas system